ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE TOBOOK VALUE DAN IMPLIKASINYA PADA RETURN SAHAM (Studi Empiris: pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Sri Wahyuni, 0835030701; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2012)
This study aimed to examine the influence of fundamental factors of the companyâs price to book value in the valuation of share s in Indonesia Stock Excange from 2008 to 2010. Sampling technique using purposive sampling that sample by using certain criteria, namely: the company gets the positive earnings and dividend consecutively in the study, is 2008-2010. Based on these criteria, then optained a sample of 34 companies. The analysis technique used is multiple linear regression analysis.The results prove that the Dividend Payout Rato (DPR) has no effect on Price to Book Value (PBV). Return On Equity (ROE) have positive and significant impact on Price to Book Value (PBV). Growth have significant negative effect on Price to Book Value (PBV). Degree Of Financial Leverage (DFL) have significant negative effect on Price to Book Value (PBV). Price to Book Value (PBV) have positive and significant impact on Stock Return.Keywords: Dividend Payout Ratio (DPR), Return on Equity (ROE), Growth, Degree of Financial Leverage (DFL), Price to Book Value (PBV), and Return Stock.